Optogenetic restoration of high sensitivity vision with bReaChES, a red-shifted channelrhodopsin - Lay Khoon Too; Weiyong Shen; Dario A. Protti; Atomu Sawatari; Dylan A. Black; Catherine A. Leamey; Jin Y. Huang; So-Ra Lee; Ashish E. Mathai; Leszek Lisowski; John Y. Lin; Mark C. Gillies; et al. (Scientific Reports, 2022)
Abstract The common final pathway to blindness in many forms of retinal degeneration is the death of the light-sensitive primary retinal neurons. However, the normally light-insensitive second- and third-order neurons persist optogenetic gene therapy aims to restore sight by rendering such neurons light-sensitive. Here, we investigate whether bReaChES, a newly described high sensitivity Type I opsin with peak sensitivity to long-wavelength visible light, can restore vision in a murine model of severe early-onset retinal degeneration. Intravitreal injection of an adeno-associated viral vector carrying the sequence for bReaChES downstream of the calcium calmodulin kinase IIα promoter resulted in sustained retinal expression of bReaChES. Retinal ganglion cells (RGCs) expressing bReaChES generated action potentials at light levels consistent with bright indoor lighting (from 13.6 log photons cm−2 s−1). They could also detect flicker at up to 50 Hz, which approaches the upper temporal limit of human photopic vision. Topological response maps of bReaChES-expressing RGCs suggest that optogenetically activated RGCs may demonstrate similar topographical responses to RGCs stimulated by photoreceptor activation. Furthermore, treated dystrophic mice displayed restored cortical neuronal activity in response to light and rescued behavioral responses to a looming stimulus that simulated an aerial predator. Finally, human surgical retinal explants exposed to the bReaChES treatment vector demonstrated transduction. Together, these findings suggest that intravitreal gene therapy to deliver bReaChES to the retina may restore vision in human retinal degeneration in vivo at ecologically relevant light levels with spectral and temporal response characteristics approaching those of normal human photopic vision.